Gastrointestinal problems in disabled children - Sullivan, P; McIntyre, E (2005)
Children with disabilities such as cerebral palsy, spina bifida or other neurological impairments frequently have associated gastrointestinal problems. These include oromotor dysfunction leading to feeding difficulties, risk of aspiration, prolonged feeding times and malnutrition with its attendant physical compromise. Gastro-oesophageal reflux disease is common in these children and may require surgical treatment. Finally, constipation is often a problem that may be overlooked in this population. This article focuses on these associated gastrointestinal manifestations and discusses the current diagnostic and therapeutic options available. © 2005 Elsevier Ltd. All rights reserved.